2017
DOI: 10.1177/0271678x17697340
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific permeability of the blood–brain barrier upon pericyte loss

Abstract: The blood-brain barrier (BBB) regulates differing needs of the various brain regions by controlling transport of blood-borne components from the neurovascular circulation into the brain parenchyma. The mechanisms underlying region-specific transport across the BBB are not completely understood. Previous work showed that pericytes are key regulators of BBB function. Here we investigated whether pericytes influence BBB permeability in a region-specific manner by analysing the regional permeability of the BBB in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 39 publications
4
84
1
Order By: Relevance
“…For context, we also examined media derived from human astrocytes, endothelial cells, and pericytes because they are known to release extracellular particles and support vascular function . Flow cytometry was performed to examine extracellular particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For context, we also examined media derived from human astrocytes, endothelial cells, and pericytes because they are known to release extracellular particles and support vascular function . Flow cytometry was performed to examine extracellular particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with pericytedeficient mice also revealed that the degree of pericyte coverage along the brain vasculature negatively correlates with barrier permeability (Armulik et al 2010;Bell et al 2010;Daneman et al 2010b). Further investigation of adult Pdgfb ret/ret pericyte-deficient mice revealed regional heterogeneity in barrier permeability, finding higher levels of permeability in the cortex, striatum, and hippocampus than in the interbrain and midbrain despite similar levels of pericyte coverage (Villaseñor et al 2016). Additional analysis with Pdgrfb +/− mice showed defects in neurovascular coupling during adulthood (Kisler et al 2017b).…”
Section: Pericytesmentioning
confidence: 97%
“…A common view is that only molecules less than 400 -500 Da in size can cross the BBB (44), but several examples of proteins that are able to cross the BBB have been described, including erythropoietin (34 kDa) (45), the exogenous tracer horseradish peroxidase (44 kDa) (30,31), and serum proteins (29). Moreover, anti-A␤ antibodies (about 150 kDa) are able to enter the brain, bind to amyloid plaques, and cause a reduction in plaque burden in AD mouse models (32,33) and in AD patients (46). BBB permeability is not the same throughout the brain, and local mechanisms may specifically regulate the transport of different molecules and proteins (47).…”
Section: Brain Penetrance Of Different Brichos Chaperone Domainsmentioning
confidence: 99%